Tanshinone IIA alleviates the damage of neurocytes by targeting GLUT1 in ischaemia reperfusion model (in vivo and in vitro experiments) - Wang, Jing; Tong, Haibo; Wang, Xiangyang; Wang, Xinxing; Wang, Yang (Folia Neuropathologica, 2020)
Stroke is partial or complete brain dysfunction combined with acute cerebral circulatory disorders, and it affects millions of individuals around the world each year. A total of 70-80% of patients experience ischaemic stroke caused by disturbances in cerebral circulation, leading to cerebral ischaemia, neuronal apoptosis, and necrosis. Tanshinone IIA is a natural compound extracted from Salvia miltiorrhiza and has been proven to assist in recovery from cerebral ischaemia reperfusion injury. GLUT1 is ubiquitously expressed in all types of tissues in the human body and has important physiological functions due to its glucose uptake ability. This experiment was performed to detect the effect of GLUT1 in promoting the therapeutic effect of tanshinone IIA. Here, we found that tanshinone IIA treatment increased the viability of neurons and promoted the recovery of brain function, and that the concentration of glucose in serum and cultured medium was also increased. We noticed that these effects might be mediated by an increased glucose uptake ability. In addition, we further found that the PI3K/mTOR/HER3 signalling pathway played an important role in regulating these effects. Thus, we thought that overexpression of GLUT1 might be an important target in the treatment of cerebral ischaemia-reperfusion.